Using the concept of activity space to understand the social health of older adults living with memory problems and dementia at home. (November 2021) - Sturge, Jodi; Klaassens, Mirjam; Lager, Debbie; Weitkamp, Gerd; Vegter, Daan; Meijering, Louise
Abstract: Globally as the population ages, the prevalence of dementia will increase. Simultaneously, there is a trend toward people ageing at home. Therefore, more people will be ageing at home with dementia, as opposed to institutional environments. In this context, there has been a recent shift in research exploring ways that people can live well with the consequences of the disease. As a part of this emerging research, the social and spatial aspects of the lives of people living with memory problems are becoming increasingly of interest. The aim of this article is to use the concept of activity space to examine the social health of older adults with memory problems and dementia who live at home. Activity space data were collected from seven older adults experiencing memory problems and living at home in the Netherlands. Using a mixed-methods approach, insight into their activity spaces were gained through walking interviews, 14 days of global positioning system (GPS) movement data, travel diary entries and in-depth interviews. The GPS data, travel diary data and interview transcripts were analyzed using a grounded visualization approach. Our findings show that participants interact independently in routine activity spaces but depend on others to participate in occasional activity spaces. Interactions within both these spaces contribute to the social health of older adults with memory problems and dementia who live at home. Additionally, participants used coping strategies and decision-making to maintain autonomy in daily life. The findings can inform dementia-friendly initiatives and social health care planning. Highlights: Older adults with memory issues and dementia engage in two activity spaces. Routine activity spaces relate to more positive social health experiences. Occasional activity spaces can both contribute to, and constrain, social health. Coping strategies and reciprocity are two indicators to measure social health.